Low Geomagnetic Field Intensity in Southern China 6,000 Years Ago - Xin Luo; Jiabo Liu; Huapei Wang; Maximilian Schanner; Yuan Zhang; Peng Xie; Jigen Tang; Peng Han; Quan Li; Fei Han; Xiaowei Chen; Chen Wen; et al. (Geophysical Research Letters)
Abstract The West Pacific Anomaly (WPA), a low geomagnetic field anomaly observed in the 16th to 18th centuries, represents a recently recognized and complex feature of Earth's magnetic field. However, the history of the WPA is still uncertain due to a scarcity of paleointensity data in Southeast Asia. Here, we conducted archeointensity analyses on pottery shards from the Xiajiaoshan site in southern China, dated to 4107 ± 123 BCE. Using Thellier–Coe and Repeated Thellier‐Series Experiment methods, we obtained high‐fidelity paleointensities ranging from 14.1 to 26.4 μT (20.7 ± 4.4 μT). These values are significantly lower than surrounding archeointensity data. We incorporated this new data into ArchKalmag14k paleomagnetic field model, which shows the presence of a geomagnetic field low‐intensity anomaly in Southeast Asia around 6,000 years ago. Our study provides the first absolute paleointensity data for low‐latitude East Asia at that time, suggesting that the WPA may have recurred approximately 6,000 years ago.